Synthesis of Manganese Tetroxide Nanoparticles Using Precipitation and Study of Its Structure and Optical Characteristics - Reza Shokoohi; Mohammad Taghi Samadi; Ghorban Asgari; Mohammad Vanaei Tabar; Kazem Godini (Hamadan University of Medical Sciences, 2016)
Considering extensive applications of manganese tetroxide nanoparticles in various industries due to its special properties, conducting studies on how to achieve more suitable ways to produce smaller nanoparticles is of great importance. In this study, nanoparticles of manganese tetroxide (Mn3O4) were synthesized by a co-precipitation method. In order to determine the characteristics of the structure, size, and specific surface of the resulting nanoparticles, techniques such as XRD, BET, BJH, FESEM, and FTIR were employed. Also, the nanoparticles were quantified with EDS and their colony size was examined using DLS experiments. The findings revealed a production of crystalline manganese tetroxide nanoparticles with a space group of 141/amd (S.G.) (141) and a molecular weight of 228.81 with the international code of ICSD Card # 89 - 4837. The specific surface area was 32.147 m2/g with a pore volume of 0.1041 cm3/g. The XRD and EDX analyses verify the production of the Mn3O4 nanoparticles. The size of the nanostructures is approximately 19 nm. The method used in this study could produce the Mn3O4 nanoparticles in a much easier way without the need for surfactants. Compared to the nanoparticles produced in other studies, the size of the nanoparticles produced in the present study is remarkably smaller. Moreover, less amount of the metal salt was used.